2010
DOI: 10.1007/s10856-010-4151-0
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo behavior of ketoprofen intercalated into layered double hydroxides

Abstract: Ketoprofen (Ket) was intercalated into layered double hydroxides (ZnAlLDH and MgAlLDH) using the ionic exchange method. The drug intercalation was confirmed by X-ray diffraction (XRD) and FTIR spectroscopy. Ket release from the inorganic matrix was studied at pH 7.4 in continuous regime with a flow rate of 0.5 and respectively 1.0 ml/min. The kinetical data were interpreted using the Ritger and Peppas model. The data prove that the release kinetics and mechanism depend on the eluent flow rate. Quantification o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…The correlation between the M 2+ /Al 3+ ratio and d 003 for PMAE and PZAE is in good agreement with that reported previously in the literature. 23 Molecular structure and spatial orientation of intercalated perindopril Figure 2A shows the three-dimensional molecular size of perindopril obtained using Chemoff ice software (Cambridge, MA). The long and short axes (the x axis and y axis, respectively) and molecular thickness (z axis) of perindopril were calculated, giving values of 13 Å, 8.4 Å, and 12.6 Å, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The correlation between the M 2+ /Al 3+ ratio and d 003 for PMAE and PZAE is in good agreement with that reported previously in the literature. 23 Molecular structure and spatial orientation of intercalated perindopril Figure 2A shows the three-dimensional molecular size of perindopril obtained using Chemoff ice software (Cambridge, MA). The long and short axes (the x axis and y axis, respectively) and molecular thickness (z axis) of perindopril were calculated, giving values of 13 Å, 8.4 Å, and 12.6 Å, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Their study revealed that Ket LDHs reduced the ulcerogenic effect to a greater extent compared to free Ket. 192 Acetylsalicylic acid-dextran-coated LDH in vivo biocompatibility Dong et al designed drug-delivery systems based on dextrancoated LDHs for acetylsalicylic acid, and conducted a pharmacokinetic study with rabbits as the model animal. 160 They found the LDH-based delivery system increased the bioavailability and half-life and reduced the side effects of acetylsalicylic acid.…”
Section: Ketoprofen Ldh In Vivo Biocompatibilitymentioning
confidence: 99%
“…Secondly, the characteristic constant for VA is one order of magnitude higher than that of GA at both pH values, showing that VA is attached to the matrix with stronger interactions. Regarding the release process, our previous studies concerning ketoprofen intercalated into LDHs have demonstrated that it occurs primarily through ion exchange between the ions belonging to the buffer solution and the intercalated drug anions [57].…”
Section: In Vitro Releasementioning
confidence: 99%